ANALISIS FAKTOR YANG MEMENGARUHI AKSEPTOR KB DALAM MEMILIH ALAT KONTRASEPSI IUD DI DESA WONOSARI KECAMATAN TANJUNG MORAWA KABUPATEN DELI SERDANG TAHUN 2012 - Pestauli Marlina Manurung; Maya Fitria; Heru Santosa (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2012)
IUD (Intra Uterine Device), a contraception placed in the uterus, is relatively more effective if compared to the methods of pills, injection and condom, and it is evident that most users choose IUD contraceptive. The purpose of this analytical study was to reduce the variables influencing the Family Planning acceptors in choosing IUD contraceptive to be a new variable which is small in number. This analytical study applied the factor analysis as a statistical aid to reduce the variables. The samples for this study were 40 persons. The result of this study showed that by using factor analysis, the 10 variables influencing the Family Planning acceptors in choosing IUD contraceptive were reduced to 7 variables (safety of IUD, availability of IUD, place of Family Planning service, health workers, information media, IUD insertion fee, and husband’s support).  Of the 7 variables, 3 factors were established such as Factor 1 including the place of Family Planning service and husband’s support is called the factor of motivation. Factor 2 including safety of IUD, availability of IUD and information media is called factor of need. Factor 3 including health workers and IUD insertion fee is called factor of socio-economy. The health workers and Family Planning field workers are expected to play an active role in increasing the awareness of couples in productive age by providing a continuous extension in order to increase the participation of couples in productive age in using IUD. Keywords: Factor Analysis, Family Planning Acceptor, IUD Contraception